Distribution of Epstein-Barr virus antigenic sites on the carboxyl terminal end of ribonucleotide reductase against nasopharyngeal carcinoma serum antibodies using an immunoabsorption method - Gan, Y.Y. (2013)
10.1002/(SICI)1096-9071(199911)59:3<385::AID-JMV20>3.0.CO;2-7